The role of media simulation in education world: A Turkish example via cern experiments - (:unkn) unknown (IGI Global, 2014)
In the last couple decades, the studies on the domination of all kinds of media in the education world became very important. Very recently, a survey of the physics teacher candidates, gymnasium students and intellectuals in Turkey have also investigated for the qualitative effects of the media in the framework of CERN Higgs particle (God particle) experiments (Saglik et al., 2012, 2013). This chapter considers the survey for Turkish physics teacher candidates given in Saglik (2013) to understand how the scientific knowledge is deconstructed by the simulation of media. © 2014 by IGI Global. All rights reserved.